Evidence for oscillating circadian clock genes in the copepod Calanus finmarchicus during the summer solstice in the high Arctic. (15th July 2020) - Hüppe, Lukas; Payton, Laura; Last, Kim; Wilcockson, David; Ershova, Elizaveta; Meyer, Bettina
Abstract : The circadian clock provides a mechanism for anticipating environmental cycles and is synchronized by temporal cues such as daily light/dark cycle or photoperiod. However, the Arctic environment is characterized by several months of Midnight Sun when the sun is continuously above the horizon and where sea ice further attenuates photoperiod. To test if the oscillations of circadian clock genes remain in synchrony with subtle environmental changes, we sampled the copepod Calanus finmarchicus, a key zooplankter in the north Atlantic, to determine in situ daily circadian clock gene expression near the summer solstice at a southern (74.5° N) sea ice-free and a northern (82.5° N) sea ice-covered station. Results revealed significant oscillation of genes at both stations, indicating the persistence of the clock at this time. While copepods from the southern station showed oscillations in the daily range, those from the northern station exhibited an increase in ultradian oscillations. We suggest that in C. finmarchicus, even small daily changes of solar altitude seem to be sufficient to entrain the circadian clock and propose that at very high latitudes, in under-ice ecosystems, tidal cues may be used as an additional entrainment cue.